2015
DOI: 10.1007/s40821-015-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of women’s labor market status on online grocery shopping, the case of Turkey

Abstract: The rate of Internet purchasing is increasing day by day. One of the reasons of that increase could be individuals' intention to allocate time effectively in order to maximize their utility function. Within this context, an employed woman would aim to spend less time on household chores such as shopping compared to the ones who are not active in the labor market. When women's age, education and other demographic characteristics are held constant, being employed for a woman is expected to have a positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…The results, which are in the second column of Table 3, are clear: First, individuals living in economically depressed postal codes tend to be less loyal and stop using the online grocery delivery service more frequently than in higher‐income postal codes. Similar patterns were found in İlhan and İşçioğlu (2015) and Kee and Wan (2004), who both concluded that, as levels of income increase, the probability of grocery shopping online also increases. Our data provides evidence of the varying purchasing power of different areas of Madrid and the differing lifestyle choices in different neighbourhoods.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The results, which are in the second column of Table 3, are clear: First, individuals living in economically depressed postal codes tend to be less loyal and stop using the online grocery delivery service more frequently than in higher‐income postal codes. Similar patterns were found in İlhan and İşçioğlu (2015) and Kee and Wan (2004), who both concluded that, as levels of income increase, the probability of grocery shopping online also increases. Our data provides evidence of the varying purchasing power of different areas of Madrid and the differing lifestyle choices in different neighbourhoods.…”
Section: Resultssupporting
confidence: 73%
“…This information must be treated carefully to understand the patterns and behaviours behind it. Some papers have used a classic set of variables to predict customer behaviour (De la Llave, López, & Angulo, 2019;_ Ilhan & _ Işçio glu, 2015;Miguéis et al, 2012;Richards, Hamilton, & Allender, 2014;Trivedi, 2011). For example, the specific date when a customer signs up for a service and the specific context of that moment may reveal something interesting about their behaviour.…”
mentioning
confidence: 99%
“…However, two studies [36,52] reported that greater household size was associated with lower online grocery use. While three studies [52][53][54] found that being employed was associated with using online grocers, one contradictory study [77] found that unemployment was associated with using online grocers.…”
Section: Characteristics Of Online Food Retail Usersmentioning
confidence: 99%
“…However, two studies [36,52] reported that greater household size was associated with lower online grocery use. While three studies [52][53][54] found that being employed was associated with using online grocers, one contradictory study [77] found that unemployment was associated with using online grocers. Female gender identity, higher income, higher education, living in an urban setting, disabilities that make it difficult to leave home, limited free time, living far from a preferred store, familiarity with online shopping, frequent shopping, and large orders were all associated with greater online grocery use.…”
Section: Characteristics Of Online Food Retail Usersmentioning
confidence: 99%
“…Her 3 kişiden 2'si zorunlu ihtiyaçlar için dışarı çıktığını belirtmiştir. Telefon ya da internet üzerinden market alışverişinin çalışanlarda ve yüksek eğitimlilerde daha sık olduğu bilinmektedir (30). Ülkemizde internet üzerinden alışveriş oldukça yaygınlaşmış olmakla birlikte market alışverişi için kullanım düşüktür (31) (25,26).…”
unclassified